THE PLACE OF REMITTANCES IN FINANCIAL FLOWS INTO DEVELOPING ECONOMIES - A. A. Tkachenko; A. B. Ginoyan (Финансы: теория и практика)
Topic. This article examines the impact of remittances on the economy of recipient countries on the basis of econometric models.Purpose. The authors set the aim to justify a point of view, according to which the influence of remittances on economic growth and investment in the CIS countries is dependent on the change of financial development variable.Methodology. The research methodology is based on the interpretation of models, which allows answering following question: how does the level of financial development in the recipient country affect the degree of influence of remittances on economic growth. For assessment of the cyclical properties of remittances’ flows, we used Hodrick-Prescott filter technique. The evaluation of this impact has been conducted in accordance with the extended version of the neoclassical model using the system generalized method of moments (S-GMM). We also used a threshold estimation as an alternative test for resistance to errors.Results. We present threshold model with a threshold parameter. We also propose a definition of pro-cyclical, counter-cyclical and acyclic remittances, based on the types of correlation between the cyclical components of real remittances and real GDP in the home countries of migrants. The resulting conclusion states that remittance has a positive impact on economic growth in less developed financial systems. Remittance de facto act as substitutes for the ‘weak’ financial services, giving people the opportunity to meet the needs in lending and insurance, which are not able to provide by the market. On the other hand, remittance has a negative impact on economic growth in countries with more developed financial sectors.Conclusions. It is concluded that in most CIS countries, remittance is pro-cyclical ones yet in varying degrees: while improving the economic situation in the migrants’ country they are more inclined to send remittance in search of investment opportunities.